+0  
 
0
217
2
avatar

0=x^4+5x^3-15x^2-5x+14

 

Anyone who can help me solve this? 

Guest Oct 21, 2017

Best Answer 

 #2
avatar+88980 
+1

x^4+5x^3-15x^2-5x+14  = 0       

 

Write -15x^2  as   -14x^2  - x^2

 

x^4+5x^3-14x^2 - x^2 -5x+14 = 0

 

x^2(x^2+ 5x - 14) - 1(x^2 + 5x - 14) = 0

 

(x^2 - 1) ( x^2 + 5x - 14) = 0

 

(x + 1) (x - 1) (x + 7) ( x - 2)  = 0

 

Set each factor to 0  and solve for x  and we get that x = -1, 1, - 7 or 2

 

 

cool cool cool

CPhill  Oct 21, 2017
 #1
avatar+26973 
0

This factorises as:

 

(x - 1)(x + 1)(x - 2)(x + 7) = 0

 

I'm sure you can take it from there!

Alan  Oct 21, 2017
 #2
avatar+88980 
+1
Best Answer

x^4+5x^3-15x^2-5x+14  = 0       

 

Write -15x^2  as   -14x^2  - x^2

 

x^4+5x^3-14x^2 - x^2 -5x+14 = 0

 

x^2(x^2+ 5x - 14) - 1(x^2 + 5x - 14) = 0

 

(x^2 - 1) ( x^2 + 5x - 14) = 0

 

(x + 1) (x - 1) (x + 7) ( x - 2)  = 0

 

Set each factor to 0  and solve for x  and we get that x = -1, 1, - 7 or 2

 

 

cool cool cool

CPhill  Oct 21, 2017

33 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.